IKTIBAR JURNALISME WARGA BAGI KOMUNITAS WARIA DI YOGYAKARTA - Adhi, Irawan Sapto; Afriati, Dwiningsih; Sari, Ade Rakhma Novita; Cahya, Fikri Nur (Ditlitabmas, Ditjen DIKTI, Kemdikbud RI, 2013)
This article aimed to describe citizen jurnalism has been used in the fight for civil and political rights. Then, describe the fulfillment civil and political rights of shemale in Yogyakarta. The results that citizen jurnalism can used as a tool in fight for civil and political rights. And the fulfillment civil rights of shemale is unfulfilled overall.